Phase composition of cathodic deposits synthesized in flinak-k2taf7-kbf4 melt - Makarova O.V.; Polyakova L.P.; Polyakov E.G.; Shevyryov A.A.; Arakcheeva A.V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The phase composition of cathodic deposits synthesized from FLINAK-K2TaF7-KBF4 melt has been studied by the X-ray diffraction method. It is shown that boron content in the electrodeposit grows as the cathodic potential is increased from peak R1 to peak R4 in the voltammogram. The scheme of changes in the phase composition depending on the increasing current density is given as follows: {β-Ta + Ta2B}R1 → {β-Ta + (Ta3B4 TaB)}R2 → TaB2R3 → {TaB2 + B}R4.